DISSEMINATED CUTANEOUS TUBERCULOSIS - D. V. Zaslavskij; Yu. S. Egorova; I. N. Chuprov; I. O. Olovyanishnikov; Ya. Yu. Gurkovskaya; A. A. Sydikov; A. L. Chuzhov; Yu. E. Ovchinnikova; I. F. Dovgalyuk; A. A. Starshinova (State Scientific Center of Dermatovenereology and Cosmetology, 2018)
Cutaneous tuberculosis is a clinically and morphologically heterogeneous group of skin diseases directly or indirectly caused by mycobacteria of the tuberculosis complex, occupying the 5th place among all localizations of extra-pulmonary tuberculosis. Manifestations of cutaneous tuberculosis are extremely diverse and depend on the immune status and ways of penetration of mycobacteria into the skin. Skin involvement can occur as a result of exogenous inoculation, contiguous spread from an adjacent focus, or hematogenous spread from other foci. Family cases of disseminated cutaneous tuberculosis are described. A combination of several clinical forms of cutaneous tuberculosis - scrofuloderma, tuberculosis cutis lichenoides (moniliformis scrophulosorum) and lupus - are observed in a 5 year old child with a family history of tuberculosis. The issues of pathogenesis and advanced methods of diagnosis of cutaneous tuberculosis are also discussed.